2014
DOI: 10.1038/ncomms4688
|View full text |Cite
|
Sign up to set email alerts
|

Silicon carbide-derived carbon nanocomposite as a substitute for mercury in the catalytic hydrochlorination of acetylene

Abstract: Acetylene hydrochlorination is an important coal-based technology for the industrial production of vinyl chloride, however it is plagued by the toxicity of the mercury chloride catalyst. Therefore extensive efforts have been made to explore alternative catalysts with various metals. Here we report that a nanocomposite of nitrogen-doped carbon derived from silicon carbide activates acetylene directly for hydrochlorination in the absence of additional metal species. The catalyst delivers stable performance durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
153
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 195 publications
(167 citation statements)
references
References 31 publications
12
153
2
Order By: Relevance
“…2a, NAC1 catalysts display very poor catalytic activity (5% conversion) for acetylene hydrochlorination reaction, while no conversion was detected in AC1. In fact, experimental studies and theoretical simulations revealed that the carbon atoms bonded with pyrrolic nitrogen atoms are the active sites have been reported by Bao's group before [26].…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…2a, NAC1 catalysts display very poor catalytic activity (5% conversion) for acetylene hydrochlorination reaction, while no conversion was detected in AC1. In fact, experimental studies and theoretical simulations revealed that the carbon atoms bonded with pyrrolic nitrogen atoms are the active sites have been reported by Bao's group before [26].…”
Section: Resultsmentioning
confidence: 82%
“…6c indicates that there is a considerable amount of acetylene desorption which covers the temperature range of 50-300°C, higher than the reaction temperature (180°C), validating the capability of NAC1 for activating acetylene directly and in line with the fact that NAC1 exhibits some activity for the hydrochlorination process. DFT study also shows that the nitrogen doping enhanced the formation of the covalent bond between C 2 H 2 and NCNT compared with the undoped CNT, and therefore promoted the addition reaction of the C 2 H 2 and HCl into C 2 H 3 Cl [26][27][28]. After a deposition of 1 wt.% Au onto the AC1 and NAC1 support, a new C 2 H 2 desorption peak appears at 250°C.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…A previous investigation by our group demonstrated that pyrrolic N ranked first in the order of nitrogen species' role for this reaction [19]. Bao et al also reported, based on experimental and theoritical results, that pyrrolic N in carbon is the active site for acetylene hydrochlorination [20]. Therefore, the pyrrolic N content of the Cu-g-C 3 N 4 /AC catalyst increased relative to that of the g-C 3 N 4 /AC catalyst, which is consistent with the catalytic activity.…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 99%